The Relationship Between Knowledge And Attitudes of The Community With The Prevention Of Draining, Burying And Closing (3M) Program against Dengue Haemorragic Fever (DHF) In Aimutin Village, Comoro Village, Dom Aleixo Sub-district, Dili District 2015 - Aniceto da Conceição Pacheco (LLDIKTI Wilayah 1, 2021)
Aedes Aegypti mosquito, often referred as Dengue Haemorrhagic Fever (DHF) cause, has a life cycle that is distinct from that of other mosquitoes. The Dengue Haemorrhagic Fever (DHF) mosquito is active between morning and evening, sucking the blood of its victims and so spreading the Dengue Haemorrhagic Fever (DHF) virus. DHF is an endemic illness, meaning that it is always prevalent in a certain geographic location or demographic group. Dengue Haemorrhagic fever preventive methods must engage the community in the form of effectively executing the draining, burying, and covering (3M) program in Aimutin Village. This study used a descriptive quantitative, cross-sectional design. The population in this study consisted of 321 heads of families, whereas the sample consisted of 39 heads of families. The sampling strategy used in this study was random sampling. Multiple correlation data analysis technique with the results of the relationship between the variable of knowledge (variable X1) and attitudes (variable X2) of the community toward implementing a draining, burying, and closing (3M) program to prevent dengue hemorrhagic fever (variable Y), the level of classification is very strong. Meanwhile, to indicate the magnitude of variable X1's contribution to variable Y with a determinant coefficient of r2x100% or 0,492x100% =24,01 %, while the remainder is impacted by other factors. Conclusions require the attention of the health minister, local leaders, and the local population in order to reactivate efforts to combat this disease.